2021
DOI: 10.3390/horticulturae7100384
|View full text |Cite
|
Sign up to set email alerts
|

The Aconitum carmichaelii F3′5′H Gene Overexpression Increases Flavonoid Accumulation in Transgenic Tobacco Plants

Abstract: Aconitum carmichaelii Debx. is a herbal species that contains many precious bioactive substances, which are alkaloids, flavonoids, steroids, and glycosides. Flavonoids, which are major secondary compounds, play an important role in maintaining redox balance in the cells of the plant body. Many flavonoids have antibacterial, antioxidant, and anticancer properties. However, studies have mainly focused on aconitine, which is a highly toxic group A poison belonging to the alkaloid group, but with little mention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In this study, the transcriptome analysis revealed that both SS and AS had an impact on the expression of genes associated with flavonoid biosynthesis ( PAL , 4CL , CHS , CHI , F3H , FLS , and F3′5′H ). Previous research has shown that overexpressing PAL , Df4CL1 , EaCHS1 , DcCHI1 , DcCHI4 , CsF3H , EkFLS , and AcF3′5′H can enhance flavonoid production in transgenic plants (Chen et al, 2015; Li et al, 2021; Mahajan & Yadav, 2014; Nguyen et al, 2021; Park et al, 2012; Wang et al, 2021; Zhu et al, 2021). Therefore, the upregulation of PAL , 4CL , CHS , CHI , F3H , FLS , and F3′5′H genes under SS, as well as the upregulation of CHS and CHI genes under AS, may contribute to increased flavonoid accumulation in grapevines, thereby enhancing their tolerance to SS and AS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the transcriptome analysis revealed that both SS and AS had an impact on the expression of genes associated with flavonoid biosynthesis ( PAL , 4CL , CHS , CHI , F3H , FLS , and F3′5′H ). Previous research has shown that overexpressing PAL , Df4CL1 , EaCHS1 , DcCHI1 , DcCHI4 , CsF3H , EkFLS , and AcF3′5′H can enhance flavonoid production in transgenic plants (Chen et al, 2015; Li et al, 2021; Mahajan & Yadav, 2014; Nguyen et al, 2021; Park et al, 2012; Wang et al, 2021; Zhu et al, 2021). Therefore, the upregulation of PAL , 4CL , CHS , CHI , F3H , FLS , and F3′5′H genes under SS, as well as the upregulation of CHS and CHI genes under AS, may contribute to increased flavonoid accumulation in grapevines, thereby enhancing their tolerance to SS and AS.…”
Section: Discussionmentioning
confidence: 99%
“…This information not only demonstrated the involvement of CpF3′5′H_2 in the response of the wild relative to herbivory but also corroborated with earlier studies from our group towards understanding the chemical basis of resistance response in C. platycarpus [ 11 ]. Though there have been studies demonstrating the utility of increased expression of F3′5′H in plants [ 21 , 24 , 25 ], deciphering the role of genes identified during the resistance response towards herbivory has been scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated the industrial utility of F3′5′H for improving colour in ornamental flowers [ 19 , 20 ]. Additionally, the overexpression of F3′5′H has also shown increased flavonoids in many plant species [ 21 ]. Further, there have also been several studies establishing the role of other pivotal enzymes of the flavonoid pathway in the management of abiotic stresses [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…F3′H, and F3′5′H which belonged to the CYP450 family played an important role in regulating the biosynthesis of different types of flavonoids. Overexpression of these genes could increase the flavonoid accumulation in plants [44]. Anthocyanins were often highly modified into anthocyanin derivatives by acyltransferase, methyltransferase, and UDP-glycosyltransferase [45].…”
Section: Discussionmentioning
confidence: 99%